Stabilizing Sustainability: In the Textile and Fashion Industry - Kirsti Reitan Andersen (Copenhagen Business School (CBS), 2017)
The publication of the Brundtland Report in 1987 put the topic of sustainable development on the political and corporate agenda. Defining sustainable development as “a development that meets the needs of the future without compromising the ability of future generations to meet their own needs” (WCED, 1987, p. 43), the Report also put a positive spin on the issue of sustainability by upholding capitalist beliefs in the possibility of infinite growth in a world of finite resources. While growth has delivered benefits, however, it has done so unequally and unsustainably. This thesis focuses on the textile and fashion industry, one of the world's most polluting industries and an industry to some degree notorious for leading the `race to the bottom' in global labour standards. Despite being faced with increasing demands to practise sustainability, most textile and fashion companies continue to fail undertake the changes that are necessary to achieve greater sustainability—or at best continue to struggle in a globalized and highly interconnected industry to implement the necessary changes. In light of this failure, this thesis investigates how organizations can change towards practising sustainability, focusing on the potential of taking a design approach to bringing about processes of organizational change.
hdl:10398/9444
Keywords: 650